Improving Local Temperature Rise in Rotational Incremental Sheet Forming Process by Modifying Forming Parameters Using Response Surface Method - 李丽华 王进 (东华大学学报（英文版）, 2017)
In rotational incremental sheet forming（ RISF） process,the friction heating of rotational tool could lead to local temperature rise of the sheet and cause the improvement of sheet＇s formability.Lightweight metal,such as magnesium alloy,could be deformed by RISF without additional heating. The objective of this study is to investigate the effects of forming parameters,namely,tool rotational speed,feed-rate,step size and wall angle,on the local temperature rise. Using response surface methodology and central composite design（ CCD） experimental design,the significance,sequence of parameters and regression models would be analyzed with AZ31 B as the experimental material,and 3D response surface plots would be shown. Combined with actual processing conditions,the measures to improve the local temperature rise by modifying each parameter would be discussed in the end. The results showed that hierarchy of the parameters with respect to the significance of their effects on the local temperature at the side wall was： feed-rate,step size,and rotational speed,while at the bottom it was： feed-rate,step size,wall angle, and rotational speed, and no significant interaction appeared. It was found that the most significant parameter was not rotational speed,but feed-rate,followed by step size,for both test positions. In addition, the local temperature would increase by elevating step size,wall angle,rotating rate,and bringing down of feed-rate.